The Efficacy of Mental Health Service on Stigma and Quality of Life of Schizophrenia in Community - Windiarti, Sri Endang; Wijayanti, Diyan Yuli (Poltekkes Kemenkes Palu, 2025)
This study was to explore the efficacy of mental health service on stigma and quality of life of schizophrenia in community. This study aims to explore the need for mental health services in the community to reduce self-stigma, community stigma and improve the quality of life of schizophrenia.The government role for the mental health care village program have not been implemented intensively. Mental health program required society participation a qualitative study of anti-stigma interventions for mental health services, which includes a step-by-step process model and strategies for implementing programs to reduce stigma and improve the quality of life for people with HIV. Data collection involved in-depth interviews with program stakeholders and direct observation of the program, and qualitative feedback from program participants. This research uses an exploratory approach with in-depth interview techniques and focus group discussions. Data analysis by using content analysis (content analysis). Finding the expected model according to the needs of the community. The analysis leads to a stage model for implementing an anti-stigma program with mental health service providers in the community, the finding of the study show that there are four themes whices Socialization of anti-stigma service program with outpatients who care for mental health, Village administrators Care for mental health, Training of cadres and mental health administrators, The mental health services needed in the community are services that are integrated with primary services and the local government, which are called mental health care villages. Family and Schizophrenia assistance with several interventions that include socializing mental health programs to families, community leaders, cadres and health workers. The service model in the mental health care village that is expected by the community is a form of intervention that aims to reduce stigma and improve the quality of life of ODS and prevent recurrence.